1968
DOI: 10.1128/aem.16.2.301-307.1968
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility of Anaerobic Ruminal Bacteria1

Abstract: This study demonstrated that 15 species of ruminal bacteria with no previous history of contact with antibiotics are susceptible to bacitracin, chloramphenicol, chlortetracycine, erythromycin, novobiocin, oleandomycin, oxytetracycline, penicillin, tetracycline, tylosin, and vancomycin. A number of the species were not inhibited by kanamycin, neomycin, polymyxin, and streptomycin. The data suggest that antibiotic-resistant cells occur within susceptible cultures of these species. Streptococcus bovis FD-10 and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
11
0

Year Published

1973
1973
2019
2019

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 11 publications
4
11
0
Order By: Relevance
“…Finally, variability between ewes 1 and 2 appeared to increase by 8 days. This increase in variability has also been seen for pure cultures with long incubation times, indicating adaptation to, or detoxification of, the AA (14).…”
Section: Resultssupporting
confidence: 54%
“…Finally, variability between ewes 1 and 2 appeared to increase by 8 days. This increase in variability has also been seen for pure cultures with long incubation times, indicating adaptation to, or detoxification of, the AA (14).…”
Section: Resultssupporting
confidence: 54%
“…Direct observations of reduced diet digestibility to feeding neomycin or oxytetracycline have not been reported in the literature, but some in vitro culture data have shown mixed results on cellulose digestibility. Fulghum et al (1968) showed major cellulolytic species of rumen bacteria were susceptible to oxytetracycline, but not neomycin. Baldwin et al (1982) reported chlortetracycline, oxytetracycline, and penicillin at 2.5 μg/mL concentrations inhibited in vitro cellulose degradation in mixed rumen cultures.…”
Section: Effects Of Antibiotics In Milk Replacer On Performance and Dmentioning
confidence: 93%
“…Studies on the resistance of rumen bacteria to antibiotics suggest that most of the common rumen species are sensitive to tetracycline (El Akkad & Hobson 1966;Fulghum et al 1968). However, recent studies on the anaerobic rumen bacterium Bacteroides ruminicola have established that at least one strain is resistant to tetracycline (Flint & Stewart 1987), furthermore this resistance is plasmid-encoded (Flint et al 1988).…”
mentioning
confidence: 99%